Climate-informed groundwater zoning in Baidoa, Somalia: Integrating RICCAR projections with TOPSIS and VIKOR - Hafsa Nuradin Mohamed; Ahmed M. Al-Areeq; Mahfuzur Rahman; Haitham Elnakar; Shakhawat Chowdhury (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Sonochemical-assisted green synthesis of wurtzite ZnO/ε-Zn(OH)2 (W- ZnO/ε-Zn(OH)2) nanoflakes using Calotropis gigantea leaves for effective photodegradation against methyl orange and supercapacitor application - Mahwish Bashir; Hafsa Mubeen; Asadullah; Mohd Saleh Al Ansari; Mirjalol Ismoilov; Tariq Mehmood; Mohammed Rafi Shaik; Mufsir Kuniyil; Mohammed Rafiq H. Siddiqui; Mujeeb Khan (Journal of Environmental Chemical Engineering, 2026)

Essential Oils and monoterpene binary mixtures as organic bioinsecticides against Callosobruchus maculatus: Bioassay, molecular docking, and dynamics insights - Hafsa Arsane; Lamyae Et-Tazy; Oussama Khibech; Hajare Errati; Meriem Outaki; Abdeslam Lamiri (Organic Agriculture, 2026)

Recycling waste for sustainability: The green synthesis of silver nanoparticles from Bougainvillea glabra green waste, and the evaluation of their antioxidant, cytotoxic, catalytic, antibacterial and in-silico molecular docking properties - Hafsa Naleem; Mathivathani Kandiah; Beneli Gunaratne; Ominda Perera (Next Research, 2026)

Unlocking Thailand's biohydrogen potential: A comparative assessment of gasification and dark fermentation using a refined approach - Hafsa Mehmood; Haseeb Akbar; Ahsan Farooq; Shabbir H. Gheewala (Biomass and Bioenergy, 2026)

Phytochemicals as Natural Therapeutics Against Helicobacter pylori: A Comprehensive Review - Syed Ali Raza Shah; Hafsa Jamil; Imtiaz Mustafa; Sumaira Sharif; Zarish Zahid; Ammar Yasir; Iffat Nayila (Current Microbiology, 2026)

Correction to: Tracing Potentially Toxic Metals from Water to Soil, Maize, and Cow Milk: Food Chain Risks and Safety Concerns - Kafeel Ahmad; Mashal Maqsood; Zafar Iqbal Khan; Asma Ashfaq; Mutiya Zafar; Muhammad Mazhar Iqbal; Ijaz Rasool Noorka; Hafsa Memona; Farzana Siddique; Ilker Ugulu (Bulletin of Environmental Contamination and Toxicology, 2026)

Exogenous salicylic acid induces GluA and PR1a defense genes and enhances tomato tolerance to combined salinity and bacterial canker stress - Jawad Ahmad; Hammad Ahmed Abbasi; Muhammad Atif; Sana Ullah; Abdullah Jalal; Zunaira Azam; Hafsa Bibi (Vegetos, 2026)

Dose–response efficacy and safety of the aldosterone synthase inhibitor baxdrostat in resistant hypertension: a systematic review and network meta-analysis - Muhammad Shahzaib; Hafsa Ali; Muhammad Roshaan; Anza Muhammad; Muhammad Yasir; Muhammad Shahryar; Nimra Afzal; Eman Shahzad (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Melitidin alleviates escitalopram-induced sub-chronic cardiotoxicity via regulating mitochondrial fission-fusion machinery and redox signaling: A biochemical, echocardiographic, and histological study - Yuting Wang; Hafsa Ashfaq; Mansour Abdulaziz Alsaleem; Mohammed Alissa; Abdullah Alghamdi; Alaa S. Alhegaili; Ahmed Al-Emam; Hesham M. Hassan (Tissue and Cell, 2026)

Dual-stream deep learning with physics-informed attention for multispectral satellite image classification - Nafisa Binte Ghulam Kibria; Hafsa Binte Kibria; Md Kishor Morol; Tze Hui Liew; Dip Nandi (Remote Sensing Applications: Society and Environment, 2026)

The rise of MXene: A new paradigm in 2D materials for energy storage devices - Muhammad Kaleem Shabbir; Javeed Akhtar; Fozia Arif; Haleema Asghar; Imamdin Chandio; Hafsa Khurshid; Khalid Hussain Thebo; Mohamed H. Helal (Journal of Environmental Chemical Engineering, 2026)

Recent developments in design and fabrication of ZIF-based materials for CO2 mitigation and environmental remediation - Hafsa Khalid; Aimon Saleem; Umer Younas; Parveen Akhter; Heena Ameen; Faisal Ali; M.I. Khan; Muhammad Pervaiz (Journal of Environmental Management, 2026)

Secondary metabolites of desert and stress-adapted plants: adaptive responses toward salinity and drought stresses, and optimization tools and techniques - Hafsa Debbagh-Nour; Fatima Zahra Briache; Ayoub El Mouttaqi; Talal Sabraoui; Marc Ducousso; Hassan Boukcim; Abdelaziz Hirich (Phytochemistry Reviews, 2026)

Integrated Viscoelastoplastic and Finite Element Analysis of Tunnel–Track Interaction in Weak Rock: Influence of Geometry and Dynamic Loading - Hafsa Farooq; Sanjay Nimbalkar (Geotechnical and Geological Engineering, 2026)
Underground railway systems provide a vital solution to urban spatial constraints, yet their construction in weak rock formations poses severe geotechnical challenges. Issues such as ground settlement and tunnel deformation under dynamic train loads can compromise structural integrity and operational safety. This study addresses these complexities by integrating a novel two-dimensional Finite Element model with a complementary viscoelastoplastic analytical framework. This dual approach effectively correlates global dynamic responses with localised continuum effects. A detailed parametric study reveals that axle loads exert a more pronounced effect on the track structure than the tunnel lining, increasing track displacement by 23.9% compared to only 12.3% for the lining. At high operational speeds, the numerical analysis identifies a stability plateau attributed to radiation damping, while the analytical model predicts a conservative upper-bound response. The analysis further demonstrates that increasing the Young’s modulus of the surrounding rock beyond 1000 MPa reduces vertical displacement to negligible levels. Geometrically, while circular cross-sections offer superior radial confinement, they exhibit an 18.5% increase in localised invert settlement compared to horseshoe profiles due to a punching shear mechanism. By establishing a mechanical hierarchy, this study provides engineers with a strategy to use analytical methods for safety baselines and numerical modelling for realistic serviceability limits.

Erratum to: CRISPR, Omics, and Nanotechnology: A Triangular Strategy for Next-Generation Wheat Improvement - Muhammad Mubashar Zafar; Ayaz Haider Khan; Ali Murtaza; Muhammad Asim Jamil; Hafsa; Muhammad Munem Khan; Muhammad Awais; Hina Firdous (Journal of Crop Health, 2026)

From gene to enzyme: Microbial engineering of bovine chymosin for efficient cheese coagulation - Hafsa Amjad; Uzma Nisar; Allah Rakha Yaseen; Faiza Saleem; Munir Ahmad; Tasuduq Yaqoob (World Journal of Microbiology and Biotechnology, 2026)

Corrigendum to “Amorphous LaAlO3-derived electrolyte: Harnessing structural disorder for high proton conductivity in LT-CFC electrolytes” [Fuel 412 (2025) 138022] - Muhammad Ahsan Masood; Sajid Rauf; Muhammad Shahid Sharif; Zuhra Tayyab; Naveed Mushtaq; MAK Yousaf Shah; Touseef Ahmad; Atif Nazar; Bushra Bibi; Aljawhara H. Almuqrin; Abdullah N. Alodhayb; Hafsa Mansha; et al. (Fuel, 2026)

Enhancing proton conduction through SLZO-LCO pn-Junction heterostructures in semiconductor ionic membrane fuel cells - Yuqi Zhou; Touseef Ahmad; Kashf Zman; Hafsa Mansha; Muhammad Faisal Anwar; Peng Zhou; Lian Chen; Haijun Wang; Yuran Qi; Yuzheng Lu (Fuel, 2026)

Integrating remote sensing, geophysical and geochemical approach for targeting intrusion-associated hydrothermal gold deposits: insights from Northeastern Desert in Egypt - Mahmoud Abd El-Rahman Hegab; Yousef M. Youssef; Kareem Hamed Abd El–Wahid; Hanaa A. Megahed; Ahmed A. El-Sheikh; Sayed A. Mohamed; Hafsa M. Atia; Heba El-Bagoury; El Sayed A. Saber (Advances in Space Research, 2026)

Biochemical and computational characterization of a recombinant catalase from Kocuria rhizophila for degradation of hydrogen peroxide in textile wastewater - Asma Zafar; Hira Mubeen; Sadaf Hameed; Mahjabeen Khan; Hafsa Sohail; Maheen Zaka; Muhammad Nauman Aftab; Anuga Liyanage (Antonie van Leeuwenhoek, 2026)

Synergistic Effects of Crop Residue Incorporation and Sesbania Green Manuring on Nitrogen Release, Ammonia Emission and Wheat Productivity in Rice-Wheat Cropping System - Hafiza Hafsa Iqbal; Sajid Mahmood; Abdul Rasul Awan; Muhammad Akhtar (Journal of Soil Science and Plant Nutrition, 2026)

Corrigendum to “Integration of ASTER remote sensing and gamma-ray spectrometry for mapping hydrothermal alteration in the Sirwa Massif, central Anti-Atlas, Morocco: A guide for mining exploration” [J. Afr. Earth Sci. 236 (2026) 106019] - Mohammed Jalal Tazi; Mohammed Ouchchen; Driss El Azzab; Driss Benyahia; Abdelhamid Bajadi; Hafsa Boufkri; Bouchra Dadi (Journal of African Earth Sciences, 2026)

Corrigendum to “Amorphous LaAlO3-derived electrolyte: Harnessing structural disorder for high proton conductivity in LT-CFC electrolytes”. [Fuel 412 (2025) 138022. doi: 10.1016/j.fuel.2025.138022] - Muhammad Ahsan Masood; Sajid Rauf; Muhammad Shahid Sharif; Zuhra Tayyab; Naveed Mushtaq; MAK Yousaf Shah; Touseef Ahmad; Atif Nazar; Bushra Bibi; Aljawhara H. Almuqrin; Abdullah N. Alodhayb; Hafsa Mansha; et al. (Fuel, 2026)

CRISPR, Omics, and Nanotechnology: A Triangular Strategy for Next-Generation Wheat Improvement - Muhammad Mubashar Zafar; Ayaz Haider Khan; Ali Murtaza; Muhammad Asim Jamil; Hafsa; Muhammad Munem Khan; Muhammad Awais; Hina Firdous (Journal of Crop Health, 2026)

Additive main effect and multiplicative interaction analysis for agronomic performances in bread wheat (Triticum aestivum L.) advanced lines across multiple environments - Hafsa Naheed; Hidayat Ur Rahman; Nadia Khan; Aziz Ur Rahman; Moez Amri; Quahir Sohail (Euphytica, 2026)

Phylogenetic and genome-wide analysis of codon usage reveals geographic and host-specific adaptation in Vaccinia virus - Hafsa Iqbal; Faisal Ahmad; Sajjad Ahmad; Iftikhar Ahmad; Muhammad Yar Sobhan Qadir; Ali Khalid; Zurva Ashraf; Zohra Ahmad; Ferjeni Zouidi (Archives of Virology, 2026)

Moringa stenopetala leaf extract improves the efficacy of doxorubicin in the breast cancer therapy by suppressing the expression of MDR-1, Raf-1, and Top-II - Mahmoud A. Al-Saman; Rehab F. Taher; Osama M. Abonama; Ibrahim A. Ibrahim; Ahmed G. Soliman; Hafsa Nour El-Din Abd El-Kader Ebrahim; Nada Elguindy; Ahmed I. Abd El Maksoud (Natural Product Research, 2026)

Assessment of heavy metals and proximate composition of a jellyfish (Rhizostoma octopus Gmelin, 1791) from Cox's Bazar coast, Bay of Bengal, Bangladesh: Tracing contamination sources and human health risks - Md. Simul Bhuyan; Debasish Pandit; Mohammad Ismail; Mir Mohammad Ali; Md Khalid Saifullah; Md. Tarikul Islam; Ahmed Harun-Al-Rashid; Ummey Hafsa Bithi; Mrityunjoy Kunda; Md. Abu Bakar Siddique (Marine Pollution Bulletin, 2026)

Amorphous LaAlO3-derived electrolyte: Harnessing structural disorder for high proton conductivity in LT-CFC electrolytes - Muhammad Ahsan Masood; Sajid Rauf; Muhammad Shahid Sharif; Zuhra Tayyab; Naveed Mushtaq; MAK Yousaf Shah; Touseef Ahmad; Atif Nazar; Bushra Bibi; Aljawhara H. Almuqrin; Abdullah N. Alodhayb; Hafsa Mansha; et al. (Fuel, 2026)

Unraveling survival disparities in primary central nervous system (CNS) lymphoma: an analysis of race, socioeconomic factors, and treatment outcomes using the surveillance, epidemiology, and end results program (2000–2021) - Shahzaib Maqbool; Mohammad Ebad Ur Rehman; Ramesha Tahir; Hafsa Arshad Azam Raja; Mouzma Ali; Muhammad Ibrahim; Jacob Guerrero; Abdur Rehman; Imran Khan; Abat Khan; Jose D. Sandoval-Sus (Cancer Causes & Control, 2026)

Assessment of genetic diversity in Abrus precatorius L. from Gujarat by using molecular indices: an initial exploration - Pooja G. Trivedi; Kush V. Prajapati; Sachin G. Prajapati; Hafsa I. Ansari; Suhas J. Vyas; Gaurang M. Sindhav (Vegetos, 2026)

Artocarpin alleviates fenofibrate-induced hepatic dysfunction via regulating NLRP3/caspase-1, oxidative stress and bile acids synthesis: A biochemical, histological, and computational investigation - Mohammed S. Alshammari; Salim Jamil; Hafsa Ashfaq; Ahmed Al-Emam; Hesham M. Hassan (Tissue and Cell, 2026)

Ayanin combats against barium sulphate nanoparticles induced hepatotoxicity via modulating SIRT1/FOXO3a and HO-1/ferritin pathways: A biochemical, histopathological and computational approaches - Di Zhu; Yuanzhi Lu; Salim Jamil; Hafsa Ashfaq; Ahmed Al-Emam; Hesham M. Hassan (Journal of Trace Elements in Medicine and Biology, 2026)

Arsenate adsorption onto hydrous ferric oxide: Insights from triple layer surface complexation modeling - Hafsa Nazir; Raheena Moozhikkal; Bhawna Thakur; Shray Pathak; Pushpendra P. Singh (Journal of Geochemical Exploration, 2026)

Integration of ASTER remote sensing and gamma-ray spectrometry for mapping hydrothermal alteration in the Sirwa Massif, central Anti-Atlas, Morocco: A guide for mining exploration - Mohammed Jalal Tazi; Mohammed Ouchchen; Driss El Azzab; Driss Benyahia; Abdelhamid Bajadi; Hafsa Boufakri; Bouchra Dadi (Journal of African Earth Sciences, 2026)

Photo-activated defect engineering unlocks high-performance proton transport in garnet electrolytes - Bushra Bibi; Atif Nazar; Muhammad Yousaf; Tanveer Farid; Rizwan Raza; Syed Asad Abbas Bukhari; Muhammad Faisal Anawar; Kashif Nazar; Hafsa Mansha; Yuzheng Lu; Bin Zhu (Chemical Engineering Journal, 2026)

Nano-cocrystal Delivery System of Curcumin: Physicochemical Characterization, Antioxidant Activity, Cytotoxicity Against MCF-7 Cells and Topical Gel Formulation - Amna saleem; Hafsa Afzal; Najam ul Hassan jawa; Sairah Hafeez Kamran; Qazi Amir Ijaz; Nasir Abbas; Sumera Latif (Journal of Pharmaceutical Innovation, 2026)

Seismic analysis of railway tunnels in weak rock formations using a viscoelastoplastic approach - Hafsa Farooq; Sanjay Nimbalkar (Bulletin of Engineering Geology and the Environment, 2026)
Underground railway tunnels are essential for urban transportation, yet they are significantly vulnerable to seismic forces, particularly in weak rock conditions. Ensuring their resilience and structural integrity during and after earthquakes is critical for operational safety and continuity. This study investigates the seismic behaviour of railway tunnels embedded in weak rock masses using a computational approach employing a novel viscoelastoplastic rheological model. The model simulates the dynamic response of the surrounding weak rock under earthquake loading, with lateral seismic forces determined via a pseudo-static method. A case study is conducted using field measurements from the Jinpingyan Tunnel, a high-speed railway tunnel situated in a seismically active region with weak rock. Parametric studies evaluate the influence of key factors, including rock mass density, primary wave (dispersion) velocity, and tunnel geometry. The study highlights the depth-dependent nature of seismic response and indicates that the tunnel geometric properties substantially impact stress distribution and deformation. This research presents a straightforward, rapid, and practical approach for evaluating the seismic vulnerability of tunnels in weak rock, offering valuable insights for optimising tunnel design and material selection to enhance the seismic resilience of underground railway systems in earthquake-prone areas.

Microalgae- and cyanobacteria-based biostimulants: Formulation strategies and patent landscape for sustainable agriculture - Hiba Elmimouni; Amer Chabili; Hafsa Foua; Mountasser Douma; Abdelilah Meddich; Mohammed Loudiki (Algal Research, 2026)

Geotechnical Rheological Modelling of Integrated Train-Track-Bridge System using a Viscoelastoplastic Approach - Hafsa Farooq; Sanjay Nimbalkar; Daichao Sheng (Computers and Geotechnics, 2026)

Efficient degradation of caffeine using silver-doped TiO2 photocatalyst: kinetics, mechanism, and process optimization via decision tree modeling - H. Hafsa; N. Nasrallah; S. Zeghbib; M. Kebir; H. Tahraoui; S. Lekmine; A. Amrane; A. Aymen Assadi; F. Fadhillah; F. Abdulraqeb Ahmed Ali (International Journal of Environmental Science and Technology, 2026)

Glabridin attenuates dibutyl phthalate-induced testicular toxicity via regulating oxidative stress, inflammation, apoptosis, and Wnt/β-catenin pathway - Hesham M. Hassan; Hafsa Ashfaq; Fuad M. Alzahrani; Khalid J. Alzahrani; Abrar Aljohani (Tissue and Cell, 2026)

Targeted renal cyto-protection by medicarpin against acyclovir-induced nephrotoxicity via regulating SIRT1/FOXO3a and endothelin axis: An experimental and computational analysis - Hesham M. Hassan; Abdulaziz Saleh Alkhoshaiban; Aqsa Bibi; Imran Abdullah; Hafsa Ashfaq; Salim Jamil; Ahmed Al-Emam (Tissue and Cell, 2026)

Cirsiliol confers cardio-protection against sunitinib induced cardiotoxicity via synergistic modulation of SIRT1/FOXO3a and endothelin axis: A biochemical, histopathological, and computational experimentation - Mahmoud El Safadi; Abdulaziz Saleh Alkhoshaiban; Hafsa Ashfaq; Giorgio Antoniolli; Ahmed Al-Emam; Hesham M. Hassan (Tissue and Cell, 2026)

Integration of life cycle sustainability assessment and process simulation to achieve an eco-design in linear alpha olefin (LAO) plant - Hafsa Mohammed Ashraf; Saad Ali Al-Sobhi; Mutaman Abdelrahim (Journal of Cleaner Production, 2026)

Disordered Pr-alumina: Enabling fast proton dynamics across energy systems - Hafsa Mansha; Touseef Ahmad; Kashf Zaman; Sajid Rauf; Muhammad Khalid; M.Ahsan Masood; Shahzad Rasool; Atif Nazar; Bushra Bibi; Nawal K. Almaymoni; Yuzheng Lu; Jun Wang; et al. (Fuel, 2026)

Complosome Activation after Myocardial Infarction in a Murine Model of Permanent LAD Ligation - Janina Ratajczak; Ahmed Abdel-Latif; Gabriela Schneider; Tahra Luther; Rajesh Chaudhary; Parisa Shabani; Rachel Lopez; Afnan Alzamrooni; Anand Prakash Singh; Hafsa Jama; Sham S. Kakar; Magdalena Kucia; et al. (Stem Cell Reviews and Reports, 2026)

Campesterol attenuates airway inflammation in allergic asthma: insights from a murine model and molecular docking analysis - Hafsa Abid; Aisha Mobashar; Arham Shabbir; Hossam Kamli; Ammara Saleem; Narmeen Mehmood; Amir Ali; Shoaib Kakar; Mohammed Dauelbait; Amir Bouallegue; Mohammad Khalid; Omar A. Almohammed (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Tracing Potentially Toxic Metals from Water to Soil, Maize, and Cow Milk: Food Chain Risks and Safety Concerns - Kafeel Ahmad; Mashal Maqsood; Zafar Iqbal Khan; Asma Ashfaq; Mutiya Zafar; Mazhar Iqbal; Ijaz Rasool Noorka; Hafsa Memona; Farzana Siddique; Ilker Ugulu (Bulletin of Environmental Contamination and Toxicology, 2026)

Exploring the Links Between Variations in Snow Cover Area and Climatic Variables Across the Upper Indus Basin Under a Changing Climate - Hafsa Muzammal; Muhammad Zaman; Jaehak Jeong; Kashif Mehmood; Syed Aftab Wajid (International Journal of Climatology, 2026)
The Upper Indus Basin (UIB) has experienced gradual changes in water supply due to variations in the Snow Cover Area (SCA) in recent decades. This study examined daily snow cover changes using satellite imagery from the Moderate Resolution Imaging Spectroradiometer (MODIS) Aqua (2002–2022) and Terra (2001–2022) via Google Earth Engine. An Auto‐regressive Integrated Moving Average (ARIMA) model was developed using time series data to predict SCA. Model accuracy was assessed using Stationarity, ACF, and PACF plots, as well as performance metrics, including AIC, BIC, RMSE, and MSE. The most appropriate iteration (0,1,1) (3,1,1) of the best‐performing model showed strong agreement between observed and simulated SCA, with R 2 values of 0.72 for calibration (2017–2020) and 0.84 for validation (2021–2023). Predicted SCA was further correlated with climate change variables (precipitation, maximum and minimum temperature) from NASA Earth Exchange (NEX) Global Daily Downscaled Projections under SSP1‐2.6 and SSP5‐8.5 scenarios. Results showed a significant decline in SCA, with moderate negative correlations ( r = −0.82 to −0.72) under SSP1‐2.6 and stronger correlations ( r = −0.99 to −0.81) under SSP5‐8.5. Precipitation showed a non‐significant correlation with SCA ( r = 0.14 ± 0.41under SSP1‐2.6; r = 0.11 ± 0.52 under SSP5‐8.5) with decreasing snow cover %. Regionally, Astore, Zanskar, Shigar, and Shingo exhibited significant SCA reductions (tau = −0.585 ± −0.002; p = 0.036 ± p ≤ 0.0001). The Indus_Downstream subbasin showed a non‐significant decreasing trend (tau = −0.002; p = 0.961). These findings highlight the challenges in maintaining runoff, hydropower generation, and freshwater storage, particularly in high‐altitude regions, due to uncertainties in SCA predictions under climate scenarios.

Characterization and pyrolysis kinetic modelling of lignocellulosic waste from rambutan seeds: A machine learning approach - Balkis Hazmi; Hafsa Farooq; Umer Rashid; Wan Azlina Wan Ab Karim Ghani; Thomas Choong Shean Yaw; Chawalit Ngamcharussrivichai; Imtiaz Ali (Biomass and Bioenergy, 2026)

An assessment of safe use and handling of agricultural pesticides by rural women in Abu Homous district of Egypt - Olfat S. Shahin; Atef M. K. Nassar; Nehal Abdel-Hakeem; Eman H. Radwan; Noha Nazeeh; Hafsa O. Hashem; Elsayed E. Hafez; Mamdoh T. Jamal; Zainab Shawky El-khalifa (International Journal of Tropical Insect Science, 2025)

Recent progress of metallic nanomaterials in energy, biomedical and environment sector - Kinza Maqsood; Sami Ullah; Asad ur Rehman; Hafsa Bashir; Syed Shoaib Ahmad Shah; Muhammad Altaf Nazir (Next Research, 2025)

Differential activation of Nrf2-Keap1 and NF-kB pathway mediates size-dependent nephrotoxicity of PM0.1, PM2.5, and PM10 particulate matter in mouse model - Sukhveer Singh; Hafsa Hashmi; Neha Singh; Priyanka Goswami; Pradeep K Singh; Mahadeo Kumar; Jyotsna Singh; Vikas Srivastava (Journal of Environmental Sciences, 2025)

Agricultural Valorisation of Treated Olive Mill Wastewater for the Cultivation of Solanum Melongena (eggplant) in Two Different Soil Environments - Abdesselam Eddaoukhi; Mohamed Berradi; Naoual El-Aouni; Hafsa Ifrah; Mohamed Allaoui; Abdessamad Eddaoukhi; Omar Berradi; Ahmed El Yacoubi; Abderrahim El Bachiri; Brahim Sallek (Water, Air, & Soil Pollution, 2025)

From Linear to Circular: Developing Comprehensive Plastics Policies in Nigeria - Fatima Hafsa; Yonas Alem; Joseph Akpokodje; Drita Dade; Ozgul Calicioglu (Circular Economy and Sustainability, 2025)

Trace Metal Contamination in Marine Fish Species: Implications for Food Safety and Human Health - Md. Samrat Mohay Menul Islam; Umme Hafsa Tuhin; Md. Ashraful Islam; Lutfunnesa Tamanna; Mahbub Alam; Muhammad Abu Bakar; Md. Manzoorul Kibria; Sreebash Chandra Battacherjee; Mohammad Shamsil Arafeen (Biological Trace Element Research, 2025)

Outbreaks of green apple aphid, Aphis pomi (De Geer) in apple orchards of Kashmir, India: Grower-Adopted management tactics and their implications for cultivation costs - Mohd Abas Shah; Sheikh Aafreen Rehman; Hafsa Ajaz Tramboo; Rifat Rasool; Wasim Hassan Raja; Sajad Un Nabi; Geetika Malik; Javid Iqbal Mir; Om Chand Sharma; Mahendra Kumar Verma (Crop Protection, 2025)

Predictive modelling of microbial contamination and antibiotic resistance risks in subway bioaerosols: correlation with environmental factors in central China - Yanjie Wang; Hafsa Yasin; Yang Liu; Haoran Zhu; Bisheng Lai (Atmospheric Pollution Research, 2025)

Structural Features South-East of the Saghro Inlier (Eastern Anti-Atlas, Morocco): Insights from Aeromagnetic Data - Zineb Aafir; Lahcen Ousaid; Mohamed Kasmi; Youssef Hahou; Soufiane Aafir; Said Courba; Assia Idrissi; Hafsa Boufkri; Ahmed Manar; Aziza Lamchaimech (Pure and Applied Geophysics, 2025)

Genomic and physiochemical characterization of two lysogenic bacteriophages, ΦCP5(17) and ΦCP17(i), infecting Clostridium perfringens - Hafsa Naseem; Zulquernain Haider; Samra Mannan; Shafiq ur Rehman (Archives of Virology, 2025)

Novel Quercetin-Ascorbic Acid Nano Cocrystals: A Carrier-free Strategy for Enhancement of Solubility, Topical Anti-oxidant Activity and Cytotoxicity - Najam ul Hassan Jawa; Nasir Abbas; Hafiza Nasreen Aslam; Hafsa Afzal; Misbah Hameed; Nadeem Irfan Bukhari; Sumera Latif (AAPS PharmSciTech, 2025)

Geospatial Analysis of Shoreline Shifts in the Indus Delta Using DSAS and Satellite Data - Hafsa Batool; Zhiguo He; Noor Ahmed Kalhoro; Xiangbing Kong (Journal of Marine Science and Engineering, 2025)
Pakistan’s coastline encompasses the Indus Delta, a critical ecosystem that sustains biodiversity, fisheries, and local livelihoods, yet it is increasingly threatened by both natural and anthropogenic pressures. This study quantifies multi-decadal shoreline changes in the Indus Delta and examines how changes in climatic factors (precipitation and wind) affect these changes, using the Digital Shoreline Analysis System (DSAS v5.1) and multi-temporal Landsat imagery (TM, ETM+, OLI) to quantify long-term shoreline dynamics from 1990 to 2020 (30-year period). Key metrics, including End Point Rate (EPR), Net Shoreline Movement (NSM), and Linear Regression Rate (LRR), indicated an overall retreat, with a mean NSM of −1810 m and a mean LRR of −173 m·year across the 30-year period. Shoreline change rates exhibited a significant relationship with climatic variables, particularly wind speed and precipitation, with dynamics shifting from erosion-dominated to localized accretion in areas where mangrove rehabilitation programs were implemented after 2005. Seasonal variability further influenced shoreline behavior: low-rainfall years intensified erosion due to reduced sediment availability, while high-rainfall years enhanced accretion through increased sediment input. These findings underscore the urgent need for integrated coastal management strategies, including mangrove conservation, sustainable sediment management, and climate-adaptive planning, to strengthen the resilience of the Indus Delta.

A Critical Review of Physiologically Based Pharmacokinetic (PBPK) Models in Liver Cirrhosis - Hafsa Hafsa; Muhammad Fawad Rasool; Faleh Alqahtani (Current Pharmacology Reports, 2025)

Multicriteria evaluation of cropland suitability using multisource datasets of satellite remote sensing and ground observation - Danish Raza; Hong Shu; Sahar Mirza; Hasnat Aslam; Aqil Tariq; Rana Waqar Aslam; Hafsa Aeman; Muhsan Ehsan; Maryam Muhammad Ali (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Viscoelastoplastic model for an integrated tunnel-track system in weak rock formations - Hafsa Farooq; Sanjay Nimbalkar (Computers and Geotechnics, 2025)

Canopy stratification, seasonal dynamics, and machine learning-based forecasting of Tetranychus urticae Koch on cucumber under polyhouse conditions - Hafsa Ajaz Tramboo; Asma Sherwani; Malik Mukhtar Ahmad; Akhtar Ali Khan; Ajaz Ahmad Malik; Ronit Jaiswal; Mohd Abas Shah (Journal of Plant Diseases and Protection, 2025)

Biocontrol of Bayoud disease: indigenous Bacillus and Actinobacteria as antagonists of Fusarium oxysporum f.sp. albedinis in date palms - Nour El Houda Rabhi; Nora Saadaoui; Naoual Bouremani; Allaoua Silini; Mohamed Abdelhafid Hamidechi; Essaid Ait Barka; Hafsa Cherif-Silini (European Journal of Plant Pathology, 2025)

Biosensors-based polypyrrole/metal-organic framework core-shell for mycotoxins detection - Mostafa Fytory; Fatma Besbes; Diana Dragoe; Rym Mlika; Waleed M.A. El Rouby; Ahmed A. Farghali; Hassan M.E. Azzazy; Hafsa Korri-Youssoufi (Analytica Chimica Acta, 2025)

Statistical analysis for the effect of meteorological factors and pollutant oxides on particulate matter using multiple linear regression model - Hafsa Saleh; Nadia Saeed; Moustafa Omar Ahmed Abu-Shawiesh; Kanwal Saleem; Ahmad Mohammad Ahmad Adawi; Hatim Solayman Migdadi (Acta Geophysica, 2025)

Rhazya stricta Decne (Apocynaceae) "Harmal": A medicinal plant with biocontrol potential against Meloidogyne incognita in tomato - Ishrat Naz; Nawaz Ali; Shah Alam Khan; Hafsa Naeem; Maria; Taimur Iqbal; Syeda Maryam Hussain; Aisha Bibi (Crop Protection, 2025)

Comparative quality assessment of plant-based kefir as a vegan alternative to traditional kefir - Hacer Meral-Aktaș; Burcu Bazu-Çırpıcı; Haktan Aktaș; Hafsa Kadi̇roğlu; Bülent Çeti̇n (Food Bioscience, 2025)

Phosphate-modified biochar attenuates cadmium availability in contaminated soil and reduces its transfer to tomato fruits - Rachida Naciri; Mohamed Chtouki; Loubna El Maalam; Hafsa Hirt; Doha Belkachach; Abdallah Oukarroum (Environmental Research, 2025)

Genome-Wide Identification and Functional Characterization of LEA4-5 Genes in Response to Drought Stress in Brassica Species - Laiba Ashfaq; Shahid Iqbal; Saeeda Rasheed; Hafsa Munir; Adnan Khan Niazi; Rao Sohail Ahmad Khan (Journal of Plant Growth Regulation, 2025)

First incidence of microplastic in commercially important food fishes and waters: A case study in the dal Lake ecosystem of North-Western Himalaya (India) - Sajad Ahmad Rather; Adnan Amin; Adnan Abubakr; Monisa Mehboob Malik; Ifra Tabassum; Mohd Ashraf Rather; Mansoor Ahmad Rather; Bhagyashree Dhekale; Ishtiyaq Ahmad; Hafsa Farooq Chashoo; Udai Ram Gurjar; Caterina Faggio (Journal of Contaminant Hydrology, 2025)

Spatial–temporal dynamics of evapotranspiration and its relationship with drivers of wetlands degradation - Hafsa Aeman; Hong Shu; Hamera Aisha; Imran Nadeem; Danish Raza (Theoretical and Applied Climatology, 2025)

Spatial, Trend, and Wavelet Analysis of AOD Over Bangladesh - Salman Tariq; Özgür Zeydan; Hafsa Shahzad; Muhammad Khan (Water, Air, & Soil Pollution, 2025)
With the rapid increase in urbanization and industrialization environmental degradation is one of the major issues of developing countries. During the last couple of years, Bangladesh has faced the poorest air quality due to this urbanization. Therefore, in this study, we used Moderate Resolution Imaging Spectroradiometer (MODIS) and Multi-angle Imaging Spectro Radiometer (MISR) retrieved Aerosol optical depth (AOD) data to investigate the spatial–temporal distribution, trend analysis, and the periodic nature of AOD over Bangladesh during the monsoon season from 2003 to 2016. Moreover, we used the Mann–Kendall test and Sen’s slope to analyze the trend analysis of aerosol during monsoon season. We also used wavelet coherence analysis (CWT) and Continuous wavelet transform (CWT) function to observe the periodic correlation of AOD with different meteorological parameters i.e., evapotranspiration, latent heat flux, precipitation, relative humidity, wind speed, and surface air temperature. The average MODIS and MISR retrieved AOD showed an increasing trend in the western regions of Bangladesh with an average value ranging from 0.27 to 0.92 and 0.13 to 0.59 respectively. AOD showed minimum values in Chittagong divisions and tends to increase towards the western region of Bangladesh. Furthermore, we observe the insignificant AOD trend during monsoon season due to high precipitation levels during June and July that washout the aerosol. Moreover, the annual variability of average AOD showed the maximum concentration of aerosols in 2008 and while minimum during 2015. Furthermore, CWT of MODIS retrieved AOD and MISR retrieved AOD shows a strong periodicity (> 0.9) during the 2nd to 4th period. MODIS AOD and MISR AOD also show a series of leading, lagging, in-phase, and anti-phase situations for all years 2003–2016, having a strong cross-wavelet transform (XWT) power ranging from 0.0 to 1. Different techniques, such as afforestation, efficient fuel usage, the development of public transport networks, etc., would be employed in light of the study’s findings to lower the concentration of particle pollution.

Correction: Salicylic Acid and Methyl Jasmonate Mitigate Cadmium Toxicity in Spinach (Spinacea oleracea L.) by Modulating Metal Translocation, Growth, Photo-Physiology and Redox Regulation - Shitosri Mondal; Md. Sabibul Haque; Md. Fazle Rabbi; Hafsa Tasnim; Atia Iffat; Artho Baroi; Md. Ashik Mia; Md. Nesar Uddin; Md. Alamgir Hossain (Journal of Soil Science and Plant Nutrition, 2025)

Prevalence of Staphylococcus aureus and Antimicrobial Drug Residues in Chicken Liver its Antibiogram Analysis and Implications on Public Health - Gulzar Ahmad; Malik Muhammad Rizwan; Faryal Azam; Muhammad Ijaz; Ainee Urooj Khan; Shamsher Khan; Muhammad Khan; Hafsa Shah; Noor Muhammad; Zia Ur Rahman; Numan Fazal; Sajjad Ullah; et al. (Indian Journal of Microbiology, 2025)

Infant mortality associated with immigration of males in a multi-level society - Samantha M. Stead; Hafsa Ishaque; Edward Mujjuzi; Julie A. Teichroeb (Behavioral Ecology and Sociobiology, 2025)

Estimation of apigenin from Abrus precatorius Linn. leaves extract by validated HPTLC densitometric method coupled with mass spectrometry - Hafsa I. Ansari; Ridham A. Dave; Pooja G. Trivedi; Almutazbellah K. Naji; Kashyap N. Thummar; Gaurang M. Sindhav (Natural Product Research, 2025)

Alternatives to conventional plastics: Polyhydroxyalkanoates (PHA) from microbial sources and recent approaches – A review - Saqib Hussain Hadri; Nida Tareen; Azka Hassan; Maha Naseer; Kabisha Ali; Hafsa Javed (Process Safety and Environmental Protection, 2025)

Unveiling exceptional conduction mechanism and high proton conductivity in amorphous electrolyte for advanced ceramic fuel cells - Touseef Ahmad; Naveed Mushtaq; Hafsa Mansha; Kashf Zaman; Muhammad Khalid; Muhammad Ahsan Masood; Muhammad Shahid Sharif; Yuzheng Lu; Bin Zhu (Fuel, 2025)

Salicylic Acid and Methyl Jasmonate Mitigate Cadmium Toxicity in Spinach (Spinacea oleracea L.) by Modulating Metal Translocation, Growth, Photo-Physiology and Redox Regulation - Shitosri Mondal; Md. Sabibul Haque; Md. Fazle Rabbi; Hafsa Tasnim; Atia Iffat; Artho Baroi; Md. Ashik Mia; Md. Nesar Uddin; Md. Alamgir Hossain (Journal of Soil Science and Plant Nutrition, 2025)

In-silico structural and functional analysis of nonsynonymous single nucleotide polymorphisms in human FOLH1 gene - Abtin Tondar; Muhammad Irfan; Sergio Sánchez-Herrero; Hafsa Athar; Aleena Haqqi; Asim Kumar Bepari; Laura Calvet Liñán; David Hervás Marin (In Silico Pharmacology, 2025)

A methodology for assessing environmental impact of building integrated PV in low carbon footprint electricity generation context - Hafsa Fares; Gabriele Lobaccaro; Nouha Gazbour; Freja Nygaard Rasmussen; David Chèze; Nolwenn Le Pierrès; Etienne Wurtz (Energy and Buildings, 2025)

Fractures analysis in the Takelsa basin (northeastern Tunisia) using field data and automatic extraction for groundwater investigation - Sabra Dhouioui; Houcem Mzali; Kalthoum Hafsa (Modeling Earth Systems and Environment, 2025)

Effects of Nickel Bioaccumulation on Hematological, Biochemical, Immune Responses, Neuroinflammatory, Oxidative Stress Parameters, and Neurotoxicity in Rats - Mohamed Yassine El Brouzi; Najlae Adadi; Mouloud Lamtai; Hafsa Boulahfa; Oussama Zghari; Nada Fath; Ayoub Rezqaoui; Abdelghafour El Hamzaoui; Smail Njimat; Aboubaker El Hessni; Abdelhalem Mesfioui (Biological Trace Element Research, 2025)

Nutritional prospects and heavy metal risks in fattened versus wild mud crabs of the Ganges-Brahmaputra delta: Implications for sustainable management - Lailatul Ferdousi; Animesh Kumar Gain; Ummey Hafsa Bithi; Mohajira Begum; Mst. Sarmina Yeasmin; Md. Abu Bakar Siddique; Nishat Tasnim; Zakaria Al Noman; Mst. Raosonara Khatun; Md. Eunus Ali Shaikh; Shamsad Sharmin; Supriya Ahmed; et al. (Aquaculture, 2025)

Corrigendum to ‘Multigenerational impact of chronic exposure to mercury chloride on maternal care, puberty, fertility, and hypothalamic function in female Mice’ [Environ. Res. 264-P2 (2025) 120396] - Meriem Laaroussi; Khadija Boukholda; Oumaima Essaidi; Laila Berroug; Hafsa Malqui; Hammou Anarghou; Hamadi Fetoui; Fatiha Chigr (Environmental Research, 2025)

Multigenerational impact of chronic exposure to mercury chloride on maternal care, puberty, fertility, and hypothalamic function in female mice - Meriem Laaroussi; Khadija Boukholda; Oumaima Essaidi; Laila Berroug; Hafsa Malqui; Hammou Anarghou; Hamadi Fetoui; Fatiha Chigr (Environmental Research, 2025)

Machine learning integration with response surface methodology to enhance the removal efficacy of arsenate (V) through sulfur-functionalized mxene coated QPPO/PVA AEM - Nimra Saher Zain; Ibrahim A. Shaaban; Farhan Zafar; Hafiz Muhammad Asif; Muhammad Tariq; Muhammad Ali Khan; Naeem Akhtar; Hafsa Kainat; Mohammad A. Assiri (Journal of Environmental Management, 2024)

Integrating MDT Tumor Board Shadowing into the Undergraduate Medical Curriculum: Perspective of Medical Students - Aasil Shayan Aziz; Masooma Shifa Rana; Salaar Ahmed; Muhammad Abdullah; Hafsa Khan Tareen; Ayesha Siddiq; Ahmed Nadeem Abbasi (Journal of Cancer Education, 2024)

Outward-rectifying potassium channels GORK and SKOR function in regulation of root growth under salt stress in Arabidopsis thaliana - Hafsa Jahan Hiya; Yoshitaka Nakashima; Airi Takeuchi; Toshiyuki Nakamura; Yoshimasa Nakamura; Yoshiyuki Murata; Shintaro Munemasa (Journal of Plant Physiology, 2024)

Ocean Wave Energy Conversion: A Review - Hafsa Bouhrim; Abdellatif El Marjani; Rajae Nechad; Imane Hajjout (Journal of Marine Science and Engineering, 2024)
The globally increasing demand for energy has encouraged many countries to search for alternative renewable sources of energy. To this end, the use of energy from ocean waves is of great interest to coastal countries. Hence, an assessment of the available resources is required to determine the appropriate locations where the higher amount of wave energy can be generated. The current paper presents a review of the resource characterizations for wave energy deployment. The paper gives, at first, a brief introduction and background to wave energy. Afterward, a detailed description of formulations and metrics used for resource characterization is introduced. Then, a classification of WECs (wave energy converters) according to their working principle, as well as PTO (power take off) mechanisms used for these WECs are introduced. Moreover, different sources for the long-term characterization of wave climate conditions are reviewed, including in situ measurements, satellite altimeters, and data reanalysis on one hand, and numerical simulations based on spectral wave models on the other hand. Finally, the review concludes by illustrating the economic feasibility of wave farms based on the use of the levelized cost of the energy index.

Unlocking NUE Potential via PASP-Ca Synergist: Insights into physio-biochemical, enzymatic and molecular analyses of contrasting potato genotypes in aeroponics - Hafsa Nazir Cheema; Ke-Xiu Wang; Haiyan Ma; Mingxia Tang; Tahseen Saba; Tingyuan Hu; Ambreen jahandad; Xiaoting Fang; Kaiqin Zhang; Muhammad Ansar; Wei He; Shunlin Zheng (Plant and Soil, 2024)

Effects of semaglutide-loaded lipid nanocapsules on metabolic dysfunction-associated steatotic liver disease - Inês Domingues; Hafsa Yagoubi; Wunan Zhang; Valentina Marotti; Espoir K. Kambale; Katlijn Vints; Malgorzata Alicja Sliwinska; Isabelle A. Leclercq; Ana Beloqui (Drug Delivery and Translational Research, 2024)
Metabolic dysfunction-associated steatotic liver disease (MASLD) is a highly prevalent chronic liver disease that can progress to end-stage conditions with life-threatening complications, but no pharmacologic therapy has been approved. Drug delivery systems such as lipid nanocapsules (LNC) are very versatile platforms that are easy to produce and can induce the secretion of the native glucagon-like peptide 1 (GLP-1) when orally administered. GLP-1 analogs are currently being studied in clinical trials in the context of MASLD. Our nanosystem provides with increased levels of the native GLP-1 and increased plasmatic absorption of the encapsulated GLP-1 analog (semaglutide). Our goal was to use our strategy to demonstrate a better outcome and a greater impact on the metabolic syndrome associated with MASLD and on liver disease progression with our strategy compared with the oral marketed version of semaglutide, Rybelsus ® . Therefore, we studied the effect of our nanocarriers on a dietary mouse model of MASLD, the Western diet model, during a daily chronic treatment of 4 weeks. Overall, the results showed a positive impact of semaglutide-loaded lipid nanocapsules towards the normalization of glucose homeostasis and insulin resistance. In the liver, there were no significant changes in lipid accumulation, but an improvement in markers related to inflammation was observed. Overall, our strategy had a positive trend on the metabolic syndrome and at reducing inflammation, mitigating the progression of the disease. Oral administration of the nanosystem was more efficient at preventing the progression of the disease to more severe states when compared to the administration of Rybelsus ® , as a suspension. Graphical abstract

Improved method for cropland extraction of seasonal crops from multi-sensor satellite data - Danish Raza; Hong Shu; Majid Nazeer; Hasnat Aslam; Sahar Mirza; Xiongwu Xiao; Azeem Sardar; Hafsa Aeman (International Journal of Remote Sensing, 2024)

Assessing the variability in chlorophyll-a and covariates in Arabian Sea using ARIMAX model and wavelet coherence approaches - Salman Tariq; Hafsa Shahzad; Zia Ul-Haq (Marine Chemistry, 2024)

Impact of glyphosate-based herbicide exposure through maternal milk on offspring’s antioxidant status, neurodevelopment, and behavior - Hammou Anarghou; Hafsa Malqui; Said Ihbour; Meriem Laaroussi; Oumaima Essaidi; Hamadi Fetoui; Mohamed Bouhrim; Mohamed Najimi; Fatiha Chigr (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Pharmacogenetic study of CES1 gene and enalapril efficacy - Misbah Hussain; Sehrish Basheer; Adila Khalil; Qurat Ul Ain Haider; Hafsa Saeed; Muhammad Faizan (Journal of Applied Genetics, 2024)

Effects of Zinc-Gluconate Levels on Growth Performance, Whole-Body Composition, and Mineral and Enzyme Activities of Juvenile Mori (Cirrhinus mrigala) - Zainab Hamid; Syed Zakir Hussain Shah; Mahroze Fatima; Maryam; Hafsa Nadeem; Wazir Ali (Biological Trace Element Research, 2024)

Unveiling the hidden hazards of smog: health implications and antibiotic resistance in perspective - Muhammad Imran Khan; Arshia Amin; Muhammad Tariq Khan; Hafsa Jabeen; Shafqat Rasul Chaudhry (Aerobiologia, 2024)

Effects of dietary nano-selenium concentration on growth, proximate chemical composition and antioxidant enzymes, and physiological responses to stressors by juvenile Catla catla - Iqra Sultan; Mahroze Fatima; Syed Zakir Hussain Shah; Noor Khan; Hafsa Nadeem; Wazir Ali (Aquaculture, 2024)

Bioaccumulation and Health Risk Assessment of Potentially Toxic Metals in Citrus Limetta & Citrus Sinensis Irrigated by Wastewater - Ilker Ugulu; Zafar Iqbal Khan; Mahrukh Mumtaz; Kafeel Ahmad; Hafsa Memona; Shehzad Akhtar; Asma Ashfaq (Bulletin of Environmental Contamination and Toxicology, 2024)

The utility of bioremediation approach over physicochemical methods to detoxify dyes discharges from textile effluents: A comprehensive review study - Hafsa Hena Sornaly; Sabbir Ahmed; Kanis Fatema Titin; Md Nahidul Islam; Anzana Parvin; Md Azizul Islam; Hossain Md Faruquee; Kamal Krishna Biswas; Rafiquel Islam; Dipak Kumar Paul; Sudhangshu Kumar Biswas (Sustainable Chemistry and Pharmacy, 2024)

Investigating power outages in Pakistan - Hafsa Ahmad; Faisal Jamil (Energy Policy, 2024)

Monitoring landuse change in Uchhali and Khabeki wetland lakes, Pakistan using remote sensing data - Rana Waqar Aslam; Hong Shu; Aqil Tariq; Iram Naz; Muhammad Nasar Ahmad; Abdul Quddoos; Kanwal Javid; Farhan Mustafa; Hafsa Aeman (Gondwana Research, 2024)

Evaluating the Effect of pH, Temperature and Concentration on Antioxidant and Antibacterial Potential of Spectroscopically, Spectrophotometrically and Microscopically Characterized Mentha Spicata Capped Silver Nanoparticles - Tahreem Tanveer; Shaukat Ali; Nazish Mazhar Ali; Muhammad Adeel Farooq; Muhammad Summer; Ali Hassan; Fareha Ali; Muhammad Irfan; Lubna Kanwal; Hafsa Shahzad; Rahila Islam (Journal of Fluorescence, 2024)

Quantifying the scale of erosion along major coastal aquifers of Pakistan using geospatial and machine learning approaches - Hafsa Aeman; Hong Shu; Hamera Aisha; Imran Nadeem; Rana Waqar Aslam (Environmental Science and Pollution Research, 2024)

Sex-specific neurobehavioral and biochemical effects of developmental exposure to Malathion in offspring mice - Laila Berroug; Meriem Laaroussi; Oumaima Essaidi; Hafsa Malqui; Hammou Anarghou; Ahmed Ait Chaoui; Mohamed Najimi; Fatiha Chigr (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Solanum tuberosum tuber-driven starch-mediated green-hydrothermal synthesis of cerium oxide nanoparticles for efficient photocatalysis and antimicrobial activities - Hafsa Siddiqui; Satendra Kumar; Palash Naidu; Shaily Gupta; Shivi Mishra; Manoj Goswami; Pramod Kumar Sairkar; Lakshmikant Atram; N. Sathish; Surender Kumar (Chemosphere, 2024)

Effects of long-term chlorpyrifos exposure on moulting and growth of Armadillo officinalis Dumèril, 1816 (Crustacea, Isopoda, Oniscidea) - Maya Moumene; Karima Hachemaoui Benmouhoub; Chafika Mouhoub Sayah; Salima Kendi; Hafsa Djoudad Kadji; Saddek Yesguer; Caroline Habold (Journal of Asia-Pacific Entomology, 2024)

Evaluation of the Effects of Wastewater Irrigation on Heavy Metal Accumulation in Vegetables and Human Health in the Cauliflower Example - Ilker Ugulu; Zafar I. Khan; Shehnaz Bibi; Kafeel Ahmad; Mudasra Munir; Hafsa Memona (Bulletin of Environmental Contamination and Toxicology, 2024)

Screening, optimization, and molecular characterization of cold-active lipase producing Bacillus cereus I13 from Arctic sediments - Hafsa Kattatheyil; Vishnupriya Sajeela; Shahana Saleena Kabeer; Akhil Prakash Ezhuthanikkunnel; Krishnan Kottekattu Padinchati; Mohamed Hatha Ammanamveetil (Biologia, 2024)

Insight into land cover dynamics and water challenges under anthropogenic and climatic changes in the eastern Nile Delta: Inference from remote sensing and GIS data - Youssef M. Youssef; Khaled S. Gemail; Hafsa M. Atia; Mohamed Mahdy (Science of The Total Environment, 2024)

Occurrence of ochratoxin A in breast milk and urine samples of nursing mothers in Bangladesh - Aporajita Das Trisha; Jaasia Momtahena Hafsa; Akibul Hasan; Ahsan Habib; Humaira Rashid Tuba; Gisela H. Degen; Nurshad Ali (Mycotoxin Research, 2024)
The mycotoxin ochratoxin A (OTA) is a potent nephrotoxin with carcinogenic properties and, thus, of concern as a food contaminant. Since food contaminant data are scarce in Bangladesh, we applied human biomonitoring to gain more insights into OTA exposure in the country’s population. OTA concentrations in human milk and urine samples of nursing mothers were determined with the aim to assess also exposure to this mycotoxin in breastfed infants. Breastfeeding mothers (n = 74) from three districts of Bangladesh (Sylhet, Cumilla, and Mymensingh region) participated in this study. They provided demographic data, along with breast milk and urine samples. OTA levels were measured by a competitive enzyme-linked immunosorbent assay (ELISA) with a detection limit of 60 ng/L for milk and 30 ng/L for urine. OTA was detected in 62.2% of all breast milk samples (mean 74.8 ± 49.0 ng/L, range < LOD–243.3 ng/L) and in 51.4% of all urine samples (mean 44.3 ± 63.5 ng/L, range < LOD–519.3 ng/L). The differences observed between regions for mean breast milk or for urinary OTA levels were relatively small. No significant correlation was observed between OTA levels in breast milk and food consumption patterns among nursing mothers. Regarding infant exposure, the estimated average daily intake of OTA for all was 15.0 ng/kg bw/day (range 4.5–45 ng/kg bw/day). In 34.5% of these infants, their estimated daily OTA intake exceeded a preliminary TDI value set by EFSA (17 ng/kg bw/day). The mean OTA intake was slightly higher (16.2 ± 7.8 ng/kg bw/day) in 1–2 months babies than in older infants (< 2 to 12 months), although the difference was not significant. Presence of OTA in most milk and urine samples of nursing mothers documents their widespread dietary mycotoxin exposure. Although based on a relatively small number of participants, the present analysis indicates non-negligible exposure of some nursed infants in Bangladesh. Therefore, further biomonitoring studies and investigations on major sources of OTA in food commodities are encouraged.

Quantitative assessment of the ethnomedicinal knowledge of wild plants used to treat human ailments - Tauseef Anwar; Huma Qureshi; Hafsa Naeem; Nagina Batool (Vegetos, 2024)

Cerium oxide nanoparticles improve the post-thaw quality and in-vivo fertility of Beetal buck spermatozoa - Mubashir Ali Khalique; Syed Murtaza Hassan Andrabi; Khalid Abdul Majeed; Muhammad Shahbaz Yousaf; Nisar Ahmad; Sajid Khan Tahir; Muhammad Hammad Fayyaz; Muhammad Shafiq Haider; Syeda Sohaila Naz; Irfan Zia Qureshi; Sulaiman Sulaiman; Hafsa Zaneb; et al. (Theriogenology, 2024)

Laser-Induced Breakdown Spectroscopy for the Identification of Microplastics Collected from Arabian Sea of Pakistan - Hafsa Yousaf; Shazia Bashir (Water, Air, & Soil Pollution, 2024)

Fabrication and Evaluation of Differential Release Bilayer Tablets of Clarithromycin and Levofloxacin by 3D Printing - Qazi Amir Ijaz; Sumera Latif; Sumaira Irum Khan; Memoona Rashid; Hafsa Afzal; Nasrullah Jan; Zeeshan Javaid; Muhammad Sarfraz; Amjad Hussain; Muhammad Sohail Arshad; Nadeem Irfan Bukhari; Nasir Abbas (Journal of Pharmaceutical Innovation, 2023)

Linear and wavelet analysis of aerosol optical depth (AOD) and prevailing meteorological factors during summer (2003–2016) over Turkey using Remote Sensing - Salman Tariq; Hafsa Shahzad; Usman Mehmood; Zia ul Haq (Air Quality, Atmosphere & Health, 2023)

Trade-offs between blue water use and greenhouse gas emissions related to food systems: An optimization study for French adults - Emmanuelle Kesse-Guyot; Philippe Pointereau; Joséphine Brunin; Elie Perraud; Hafsa Toujgani; Florine Berthy; Benjamin Allès; Mathilde Touvier; Denis Lairon; François Mariotti; Julia Baudry; Hélène Fouillet (Sustainable Production and Consumption, 2023)

Diversity of complex polysaccharide degrading bacteria from the sediments of interlinked high Arctic fjords, Svalbard - Vishnupriya S.; Jabir T.; Adarsh B.M.; Hafsa Kattatheyil; Shahana Kabeer S.; Krishnan K.P.; Radhakrishnan C.K.; Mohamed Hatha A.A. (Regional Studies in Marine Science, 2023)

A review of membrane-based dewatering technology for the concentration of liquid foods - Mona Gulied; Khulood Logade; Hafsa Mutahir; Sadiyah Shaftah; Sayma Salauddin; Areeba Hameed; Sifani Zavahir; Tasneem Elmakki; Ho Kyong Shon; Seungkwan Hong; Hyunwoong Park; Dong Suk Han (Journal of Environmental Chemical Engineering, 2023)

Analysis of aerosol optical depth and relation to covariates during pre-monsoon season (2002–2019) over Pakistan using ARIMAX model and cross-wavelet analysis - Yunpeng Sun; Pengpeng Gao; Salman Tariq; Hafsa Shahzad; Usman Mehmood; Zia ul Haq (Environmental Research, 2023)

Characterization of L-asparaginase from Streptomyces koyangensis SK4 with acrylamide-minimizing potential in potato chips - S Shahana Kabeer; Bini Francis; S Vishnupriya; Hafsa Kattatheyil; K.J Joseph; K.P Krishnan; A. A Mohamed Hatha (Brazilian Journal of Microbiology, 2023)

Experiments and geochemical modelling of arsenic interaction with clay-dominated soil from Rupnagar district of Punjab, India - Hafsa Nazir; Vijay A. Loganathan (Water Security, 2023)

Climate Change Impact on Land Use and Land Cover Change on Saint Martin's Island, Bangladesh - Raju Ahmed; Khandakar Hasan Mahmud; Bibi Hafsa; Jannatun Hussna Tuya; Ehasan Reza; Ummul Momanin Coalee (Journal of Coastal Conservation, 2023)

Therapeutic and immunomodulatory role of probiotics in breast cancer: A mechanistic review - Muhammad Summer; Shaukat Ali; Umaima Fiaz; Hafiz Muhammad Tahir; Muhammad Ijaz; Shumaila Mumtaz; Rabia Mushtaq; Rida Khan; Hafsa Shahzad; Hashim Fiaz (Archives of Microbiology, 2023)

Sinking delta: Quantifying the impacts of saltwater intrusion in the Indus Delta of Pakistan - Hafsa Aeman; Hong Shu; Sawaid Abbas; Hamera Aisha; Muhammad Usman (Science of The Total Environment, 2023)

Elicitor mediated enhancement of shoot biomass and lupeol production in Hemidesmus indicus (L.) R. Br. ex. Schult. and Tylophora indica (Burm. F.) Merrill using yeast extract and salicylic acid - Ashutosh R. Pathak; Swati R. Patel; Aruna G. Joshi; Neeta Shrivastava; Gaurang Sindhav; Sonal Sharma; Hafsa Ansari (Natural Product Research, 2023)

Use of dietary β-mannanase supplementation to increase nutrient digestibility and improve growth of juvenile rohu (Labeo rohita) given a feed based on plant ingredients - Rimsha Saleem; Syed Zakir Hussain Shah; Mahroze Fatima; Maryam; Hafsa Nadeem (Aquaculture International, 2023)

Effect of the Catalyst Support on Dye Degradation Using Advanced Oxidation Processes Treatment: Application of the Fractional Factorial Design - Hafsa Rabah; Khadidja Khaldi; Mostapha Zerrouki; Mounir Mekidiche; Djahida Lerari-Zinai; Khaldoun Bachari; Abderrahim Choukchou-Braham (Water, Air, & Soil Pollution, 2023)

The expression of liver TNF-α gene, liver and small intestine histology of thermal stressed growing rabbits affected by allicin and lycopene - Yassmine M. El-Gindy; Salma H. Abu Hafsa; Nehal M. El-Deeb (Journal of Thermal Biology, 2023)

Green hydrogen and sustainable development – A social LCA perspective highlighting social hotspots and geopolitical implications of the future hydrogen economy - Malik Sajawal Akhtar; Hafsa Khan; J. Jay Liu; Jonggeol Na (Journal of Cleaner Production, 2023)

Neurological monitoring in ECMO patients: current state of practice, challenges and lessons - Hassan Aboul-Nour; Ammar Jumah; Hafsa Abdulla; Amreeta Sharma; Bradley Howell; Namita Jayaprakash; Jayna Gardner-Gray (Acta Neurologica Belgica, 2023)

Comparative analysis of genetic diversity, growth performance, disease resistance and expression of growth and immune related genes among five different stocks of Labeo rohita (Hamilton, 1822) - Muhammad Kamran; Hafsa Razzaq; Muhammad Noorullah; Muhammad Ahmad; Amina Zuberi (Aquaculture, 2023)

Summertime variability of aerosols and covariates over Saudi Arabia using remote sensing - Salman Tariq; Hafsa Shahzad; Usman Mehmood; Zia ul-Haq (Air Quality, Atmosphere & Health, 2023)

The Combined Effect of Beetroot Peel Extract, Chilling, and Vacuum Packaging on the Shelf-Life of Deccan Mahseer ( Tor khudree ) Steaks - Hafsa Maqbool; Zynudheen Abubacker; Muhammad P. Safeena; Mudassir Azhar; C.G. Joshy (Journal of Aquatic Food Product Technology, 2023)

Rapid method for detection, quantification and measuring microbial degradation of pesticide-thiram using high performance thin layer chromatography (HPTLC) - Sonalkunwar Chouhan; Rinkal Mulani; Hafsa Ansari; Gaurang Sindhav; Priyashi Rao; Rakesh M. Rawal; Meenu Saraf; Dweipayan Goswami (Environmental Science and Pollution Research, 2023)

Impact of Probiotic Geotrichum candidum QAUGC01 on Health, Productivity, and Gut Microbial Diversity of Dairy Cattle - Shahid Zaman; Madeeha Gohar; Hafsa Kanwal; Afia Chaudhary; Muhammad Imran (Current Microbiology, 2022)

Expression profiling of HSP 70 and interleukins 2, 6 and 12 genes of Barki sheep during summer and winter seasons in two different locations - Raed A. Abu Rawash; Mahmoud A. Sharaby; Gamal El-Din A. Hassan; Alaa E. Elkomy; Elsayed E. Hafez; Salma H. Abu Hafsa; Mohamed M. I. Salem (International Journal of Biometeorology, 2022)
The objectives of this research were to contrast the expression values of heat shock protein (HSP70) and interleukins 2, 6 and 12 (IL 2, IL 6 and IL 12) genes in summer and winter in two different locations in Egypt (Alexandria zone and Matrouh zone) to deduce changes in thermo-physiological traits and biochemical blood metabolites of Barki sheep. A total of 50 ewes (20 in Alexandria and 30 in Matrouh) were individually blood sampled to determine plasma total protein (TP), Albumin, Globulin and Glucose constituents and T3, T4 and cortisol hormones. The thermo-physiological parameters of rectal temperature (RT, °C), skin temperature (ST, °C), Wool temperature (WT, °C), respiration rate (RR, breaths/min) and pulse rate (PR, beats/min) were measured for each ewe. Expressions of IL 2, IL 6, IL 12 and HSP 70 in summer and winter were analyzed along with thermo-physiological parameters and blood biochemical metabolites. In both locations, THI had significant effects on ST, WT, PR and RR, but not significant on RT. However, it had no significant effects on blood plasma metabolites and hormonal concentrations in the two locations in summer and winter. In Alexandria location, THI had negative significant effect on the expressions of IL-2 and IL-6 but positively affected on HSP70 genes in winter, while the expression of IL-12 gene was not affected by seasons, whereas in Matrouh zone, the effects of THI on the expressions of all tolerance genes were not significant. The results of the current study suggest that IL-2, IL-6 and HSP70 genes could be used as molecular markers for heat/cold stress.

SHANK3 genetic polymorphism and susceptibility to ASD: evidence from molecular, in silico, and meta-analysis approaches - Hafsa Siddiqua; Yasmin Akter; Md. Nasir Uddin; Mahadia Kumkum; Mohammad Afzal Hossain; Md. Abdul Aziz; Mst. Sharika Ahmed; Mahmood Ahmed Chowdhury; Mohammad Safiqul Islam; Lolo Wal Marzan (Molecular Biology Reports, 2022)

Efficacy of Biochar-Supplemented Soil for Modification of Physio-Biochemical Attributes of Canola (Brassica napus L.) Genotypes under Different Moisture Regimes - Hafsa Shakeel; Summera Jahan; Khadija Rafiq; Sumera Iqbal; Fahd Rasul (Journal of Soil Science and Plant Nutrition, 2022)

Landslide susceptibility mapping of Rangamati District of Bangladesh using statistical and machine intelligence model - Bibi Hafsa; Md. Sharafat Chowdhury; Md. Naimur Rahman (Arabian Journal of Geosciences, 2022)

Landslide Susceptibility Mapping Using Bivariate Statistical Models and GIS in Chattagram District, Bangladesh - Md. Sharafat Chowdhury; Bibi Hafsa (Geotechnical and Geological Engineering, 2022)

Nutrient Profile of Wild Black Soldier Fly (Hermetia illucens) Prepupae Reared on Municipal Dustbin’s Organic Waste Substrate - Lailatul Ferdousi; Nahid Sultana; Ummey Hafsa Bithi; Sharmin Akter Lisa; Md. Rakibul Hasan; Md. Abu Bakar Siddique (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2022)

Enhanced expression of plasma membrane intrinsic protein 2 improves cotton fiber length in Gossypium arboreum - Hafsa Amat-ur-Rasool; Ayesha Latif; Aneela Yasmeen; Naila Shahid; Saira Azam; Aftab Bashir; Tayyab Husnain; Abdul Qayyum Rao; Wayne G. Carter; Ahmad Ali Shahid (Molecular Biology Reports, 2022)

Knowledge, attitude, and practice of clinicians about antimicrobial stewardship and resistance among hospitals of Pakistan: a multicenter cross-sectional study - Sohaib Ashraf; Shoaib Ashraf; Moneeb Ashraf; Muhammad Ahmad Imran; Zawar Ahmad Choudhary; Hadiqa Tul Hafsa; Abeer Bin Awais; Larab Kalsoom; Iqra Farooq; Zaighum Habib; Sidra Ashraf; Qurrat Ul Ain Iqbal; et al. (Environmental Science and Pollution Research, 2022)

Multiple Functional Brain Networks Related to Pain Perception Revealed by fMRI - Matteo Damascelli; Todd S. Woodward; Nicole Sanford; Hafsa B. Zahid; Ryan Lim; Alexander Scott; John K. Kramer (Neuroinformatics, 2022)
The rise of functional magnetic resonance imaging (fMRI) has led to a deeper understanding of cortical processing of pain. Central to these advances has been the identification and analysis of “functional networks”, often derived from groups of pre-selected pain regions. In this study our main objective was to identify functional brain networks related to pain perception by examining whole-brain activation, avoiding the need for a priori selection of regions. We applied a data-driven technique—Constrained Principal Component Analysis for fMRI (fMRI-CPCA)—that identifies networks without assuming their anatomical or temporal properties. Open-source fMRI data collected during a thermal pain task (33 healthy participants) were subjected to fMRI-CPCA for network extraction, and networks were associated with pain perception by modelling subjective pain ratings as a function of network activation intensities. Three functional networks emerged: a sensorimotor response network, a salience-mediated attention network, and the default-mode network. Together, these networks constituted a brain state that explained variability in pain perception, both within and between individuals, demonstrating the potential of data-driven, whole-brain functional network techniques for the analysis of pain imaging data.

Identifications and geodynamic implications of magnetic structures of the Oujda-Debdou-Guercif zone (North-Eastern of Morocco): Analysis and processing of aeromagnetic data - Hafsa Boufkri; Driss El Azzab; Abdelhalim Miftah; Charroud Mohammed (Arabian Journal of Geosciences, 2021)

Comparative efficacy of Ovaprim and hMG (menotropin) to induce breeding in African catfish (Clarias gariepinus) - Muhammad Wajahat Ameer; Farhat Jabeen; Muhammad Asad; Ghazala Kaukab; Amnah Bashir; Misha Rasheed; Hafsa Younis; Naveed Munir; Javaria Nawaz; Rida Zainab; Muhammad Akram (Fish Physiology and Biochemistry, 2021)

Occurrence of aflatoxin M1 in human breast milk in Bangladesh - Farjana Islam; Aporajita Das Trisha; Jaasia Momtahena Hafsa; Akibul Hasan; Gisela H. Degen; Nurshad Ali (Mycotoxin Research, 2021)

High Blood Lead Levels: An Increased Risk for Development of Brain Hyperintensities among Type 2 Diabetes Mellitus Patients - Hafsa Suhail Najim Al-Anbari; Dawser K. Ismail; Mohammed Khudair Hasan; Qutaiba Ahmed Al Khames Aga; Pottathil Shinu; Anroop B. Nair (Biological Trace Element Research, 2021)

Improvement of Medicago sativa Crops Productivity by the Co-inoculation of Sinorhizobium meliloti–Actinobacteria Under Salt Stress - Samira Saidi; Hafsa Cherif-Silini; Ali Chenari Bouket; Allaoua Silini; Manal Eshelli; Lenka Luptakova; Faizah N. Alenezi; Lassaad Belbahri (Current Microbiology, 2021)
Biotic and abiotic stresses are severely limiting plant production and productivity. Of notable importance is salt stress that not only limits plant growth and survival, but affects the soil fertility and threatens agricultural ecosystems sustainability. The problem is exacerbated in fragile arid and semi-arid areas where high evaporation, low precipitation and the use of salty water for irrigation is accelerating soil salinization. Legumes, considered very nutritious foods for people and providing essential nutrients for ecosystems are a fundamental element of sustainable agriculture. They can restore soil health by their ability to fix nitrogen in a symbiotic interaction with the rhizobia of the soil. However, salt stress is severely limiting productivity and nitrogen fixation ability in legumes. Plant growth-promoting rhizobacteria (PGPR) and mainly actinobacteria promote plant growth by producing phytohormones, siderophores, antibiotics and antifungal compounds, solubilizing phosphate and providing antagonism to phytopathogenic microorganisms. In addition, actinobacteria have beneficial effects on nodulation and growth of legumes. In this study, actinobacteria isolated from different niches and having PGP activities were used in co-inoculation experiments with rhizobia in Medicago sativa plants rhizosphere submitted to salt stress. The results indicate that drought- and salinity-tolerant Actinobacteria with multiple PGP traits can potentially increase alfalfa growth under saline conditions, in the presence or absence of symbiotic rhizobial bacteria. Actinobacteria discovered in this study can, therefore, be suitable biofertilizers in the formulation of agricultural products improving plant development, health and productivity in saline soils, a necessary alternative for modern agriculture and sustainable development.

A comparative study of RC bridge for evaluation of seismic performance and retrofit technology - Hafsa Farooq (Innovative Infrastructure Solutions, 2021)

Physicomechanical, stability, and pharmacokinetic evaluation of aceclofenac dimethyl urea cocrystals - Hafsa Afzal; Nasir Abbas; Amjad Hussain; Sumera Latif; Kanwal Fatima; Muhammad Sohail Arshad; Nadeem Irfan Bukhari (AAPS PharmSciTech, 2021)

Antioxidant Properties and the Preservative Effect of Whole Radish Extract on Quality of Deccan Mahseer ( Tor khudree ) Steaks during Chilled Storage - Hafsa Maqbool; Zynudheen Abubacker; Safeena M.P.; Sathish Kumar (Journal of Aquatic Food Product Technology, 2020)

“It’s not just cricket”—exploring the expectations and experiences of the connoisseur sport tourist - Richard Keith Wright; Jason Doyle; Hafsa Ali (German Journal of Exercise and Sport Research, 2020)

Single or Combined Applications of Zinc and Multi-strain Probiotic on Intestinal Histomorphology of Broilers Under Cyclic Heat Stress - Muqader Shah; Hafsa Zaneb; Saima Masood; Rifat Ullah Khan; Muhammad Mobashar; Imad Khan; Salahud Din; Muhammad Shoaib Khan; Habib Ur Rehman; Antonella Tinelli (Probiotics and Antimicrobial Proteins, 2020)

Potential perspectives of biodegradable plastics for food packaging application-review of properties and recent developments - Muhammad Imran Din; Tayabba Ghaffar; Jawayria Najeeb; Zaib Hussain; Rida Khalid; Hafsa Zahid (Food Additives & Contaminants: Part A, 2020)

Determination of antioxidant activity, total phenolics and fatty acids in essential oils and other extracts from callus culture, seeds and leaves of Argania spinosa (L.) Skeels - Meriyem Koufan; Ilham Belkoura; Mouaad Amine Mazri; Abderrahim Amarraque; Amine Essatte; Hafsa Elhorri; Fatima Zaddoug; Tajlmolk Alaoui (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

Environmental risk assessment of diclofenac residues in surface waters and wastewater: a hidden global threat to aquatic ecosystem - Hafsa Hanif; Amir Waseem; Sundas Kali; Naveeda Akhtar Qureshi; Muhammad Majid; Mazhar Iqbal; Tofeeq Ur-Rehman; Muhammad Tahir; Sohail Yousaf; Muhammad Mazhar Iqbal; Imtiaz Ahmad Khan; Mazhar Iqbal Zafar (Environmental Monitoring and Assessment, 2020)

Elucidating the ecological networks in stone‐dwelling microbiomes - Moussa Louati; Nathaniel J. Ennis; Faten Ghodhbane‐Gtari; Karima Hezbri; Joseph L. Sevigny; Maria F. Fahnestock; Hafsa Cherif‐Silini; Julia G. Bryce; Louis S. Tisa; Maher Gtari (Environmental Microbiology, 2020)
Summary Stone surfaces are extreme environments that support microbial life. This microbial growth occurs despite unfavourable conditions associated with stone including limited sources of nutrients and water, high pH and exposure to extreme variations in temperature, humidity and irradiation. These stone‐dwelling microbes are often resistant to extreme environments including exposure to desiccation, heavy metals, UV and Gamma irradiation. Here, we report on the effects of climate and stone geochemistry on microbiomes of Roman stone ruins in North Africa. Stone microbiomes were dominated by Actinobacteria, Cyanobacteria and Proteobacteria but were heavily impacted by climate variables that influenced water availability. Stone geochemistry also influenced community diversity, particularly through biologically available P, Mn and Zn. Functions associated with photosynthesis and UV protection were enriched in the metagenomes, indicating the significance of these functions for community survival on stones. Core members of the stone microbial communities were also identified and included Geodermatophilaceae, Rubrobacter , Sphingomonas and others. Our research has helped to expand the understanding of stone microbial community structure and functional capacity within the context of varying climates, geochemical properties and stone conditions.

Analysis of meteorological drought sequences at various timescales in semi-arid climate: case of the Cheliff watershed (northwest of Algeria) - Faiza Hallouz; Mohamed Meddi; Gil Mahé; Salaheddine Ali Rahmani; Hafsa Karahacane; Samiha Brahimi (Arabian Journal of Geosciences, 2020)

Effect of Dietary Supplementation of Zinc and Multi-Microbe Probiotic on Growth Traits and Alteration of Intestinal Architecture in Broiler - Muqader Shah; Hafsa Zaneb; Saima Masood; Rifat Ullah Khan; Saima Ashraf; Arbab Sikandar; Hafiz Faseeh Ur Rehman; Habib Ur Rehman (Probiotics and Antimicrobial Proteins, 2019)

Gestational and Lactational Exposure to Malathion Affects Antioxidant Status and Neurobehavior in Mice Pups and Offspring - Fatima Zahra Ouardi; Hammou Anarghou; Hafsa Malqui; Nabila Ouasmi; Mohammed Chigr; Mohamed Najimi; Fatiha Chigr (Journal of Molecular Neuroscience, 2019)

Evaluation of Potential Toxic Metals Accumulation in Wheat Irrigated with Wastewater - Kafeel Ahmad; Kinza Wajid; Zafar Iqbal Khan; Ilker Ugulu; Hafsa Memoona; Madiha Sana; Khalid Nawaz; Ifra Saleem Malik; Humayun Bashir; Muhammad Sher (Bulletin of Environmental Contamination and Toxicology, 2019)

Toxicological potential of cobalt in forage for ruminants grown in polluted soil: a health risk assessment from trace metal pollution for livestock - Zafar Iqbal Khan; Nimra Arshad; Kafeel Ahmad; Muhammad Nadeem; Asma Ashfaq; Kinza Wajid; Humayun Bashir; Mudasra Munir; Bushra Huma; Hafsa Memoona; Madiha Sana; Khalid Nawaz; et al. (Environmental Science and Pollution Research, 2019)

An integrated approach for understanding the high infection rates of olive viruses in Tunisia - Mohamed Salem Zellama; Carla M. R. Varanda; Patrick Materatski; Nesrine Nabi; Ahmed Ben Hafsa; Besma Mrabet Saamali; Maher Chaouachi; Maria R. Félix (European Journal of Plant Pathology, 2019)

Trend analysis of rainfall and drought over the Oum Er-Rbia River Basin in Morocco during 1970–2010 - Hamza Ouatiki; Abdelghani Boudhar; Aziz Ouhinou; Abdelkrim Arioua; Mohammed Hssaisoune; Hafsa Bouamri; Tarik Benabdelouahab (Arabian Journal of Geosciences, 2019)

Continuous Exposure to Inorganic Mercury Affects Neurobehavioral and Physiological Parameters in Mice - Hafsa Malqui; Hammou Anarghou; Fatima Zahra Ouardi; Nabila Ouasmi; Mohamed Najimi; Fatiha Chigr (Journal of Molecular Neuroscience, 2018)

Determination of mosquito Larvicidal potential of Bacillus thuringiensis Cry11Ba fusion protein through molecular docking - Rabbia Pervaiz; Mohsin Ahmad Khan; Nadeem Ahmed; Hafsa Naeem; Ahmad Usman Zafar (Biologia, 2018)

Simultaneously Improving Mechanical, Formulation, and In Vivo Performance of Naproxen by Co-Crystallization - Nasir Abbas; Sumera Latif; Hafsa Afzal; Muhammad Sohail Arshad; Amjad Hussain; Saleha Sadeeqa; Nadeem Irfan Bukhari (AAPS PharmSciTech, 2018)

Status of potato viruses in Tunisia and molecular characterization of Tunisian Potato Virus X (PVX) isolates - Ahmed Ben Hafsa; Nesrine Nabi; Besma M’rabet Saamali; Mohammed Salem Zellama; Sébastien Theil; Chantal Faure; Aurélie Berard; Dominique Brunel; Marie-Christine Le Paslier; Armelle Marais; Thierry Candresse; Maher Chaouachi (European Journal of Plant Pathology, 2018)

Erratum to: Sub-chronic exposure to low concentration of dibutyl phthalate affects anthropometric parameters and markers of obesity in rats - Khalid Abdul Majeed; Habib ur Rehman; Muhammad Shahbaz Yousaf; Hafsa Zaneb; Imtiaz Rabbani; Sajid Khan Tahir; Muhammad Afzal Rashid (Environmental Science and Pollution Research, 2017)

Sub-chronic exposure to low concentration of dibutyl phthalate affects anthropometric parameters and markers of obesity in rats - Khalid Abdul Majeed; Habib ur Rehman; Muhammad Shahbaz Yousaf; Hafsa Zaneb; Imtiaz Rabbani; Sajid Khan Tahir; Muhammad Afzal Rashid (Environmental Science and Pollution Research, 2017)

Exploring geospatial techniques for spatiotemporal change detection in land cover dynamics along Soan River, Pakistan - Hafsa Bashir; Sheikh Saeed Ahmad (Environmental Monitoring and Assessment, 2017)

Polyaniline films for efficient removal of aromatic acids from water - Mohamed Laabd; Hafsa Chafai; Nouh Aarab; Abdelhadi El Jaouhari; Mohammed Bazzaoui; Hassan Kabli; Habiba Eljazouli; Abdallah Albourine (Environmental Chemistry Letters, 2016)

Diazotrophs-assisted phytoremediation of heavy metals: a novel approach - Abid Ullah; Hafsa Mushtaq; Hazrat Ali; Muhammad Farooq Hussain Munis; Muhammad Tariq Javed; Hassan Javed Chaudhary (Environmental Science and Pollution Research, 2015)

Development of real-time PCR method for the detection and the quantification of a new endogenous reference gene in sugar beet “Beta vulgaris L.”: GMO application - Maher Chaouachi; Akram Alaya; Imen Ben Haj Ali; Ahmed Ben Hafsa; Nesrine Nabi; Aurélie Bérard; Marcel Romaniuk; Fethia Skhiri; Khaled Saïd (Plant Cell Reports, 2013)

Characterization of structure and activity of garlic peroxidase (POX1B) - Sarra El Ichi; Anna Miodek; Hélène Sauriat-Dorizon; Jean-Pierre Mahy; Céline Henry; Mohamed Nejib Marzouki; Hafsa Korri-Youssoufi (JBIC Journal of Biological Inorganic Chemistry, 2011)

Kinetics of the electron transfer reaction of Cytochrome c 552 adsorbed on biomimetic electrode studied by time-resolved surface-enhanced resonance Raman spectroscopy and electrochemistry - Sophie Bernad; Nadine Leygue; Hafsa Korri-Youssoufi; Sophie Lecomte (European Biophysics Journal, 2007)

Phytochemical studies and antibacterial activity of Centaurium pulchellum Druce - Hafsa Bibi; Irshad Ali; S. K. Sadozai; Atta-Ur-Rahman (Natural Product Research, 2006)

Microperoxidase 8 adsorbed on a roughened silver electrode as a monomeric high-spin penta-coordinated species: characterization by SERR spectroscopy and electrochemistry - Sophie Lecomte; Remy Ricoux; Jean Pierre Mahy; Hafsa Korri-Youssoufi (JBIC Journal of Biological Inorganic Chemistry, 2004)